Analysis of Question Difficulty Levels Based on Science Process Skills Indicators Using the Rasch Model - Isnawati, Isnawati; Sriyati, Siti; Agustin, Rika Rafika; Supriyadi, Supriyadi; Kasi, Yohanes F; Ismail, Ismail (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2024)
This study analyzed the difficulty level of a science process skills test using the Rasch Model. Conducted with high school students, the study employed a quasi-experimental design with pretest and posttest assessments to measure changes in nine indicators of science process skills following an educational intervention. The intervention, an e-module on climate change based on place-based education, was integrated into the science curriculum. Results showed significant improvements in students' abilities across all indicators, with initially challenging questions becoming easier post-intervention. These findings underscore the effectiveness of e-modules in enhancing science process skills such as observing, communicating, interpreting, predicting, classifying, asking questions, applying concepts, formulating hypotheses, and planning experiments. The analysis using the Rasch Model indicated a decrease in question difficulty levels from a positive measure value in the pretest (+2.13) to a negative measure value in the posttest (-2.13). The greatest improvements were observed in the indicators for formulating hypotheses (question 8) and planning experiments (question 9), with differences of -7.91 and -7.15, respectively. This study highlights the utility of the Rasch Model in educational assessment and the potential for targeted educational interventions to enhance student performance and learning outcomes in science education.